ChemInform Abstract: Main Challenges for High Performance NAS Battery: Materials and Interfaces. Issue 19 (18th April 2013) - Wen, Zhaoyin; Hu, Yingying; Wu, Xiangwei; Han, Jinduo; Gu, Zhonghua
Abstract Review: research progress and application of Na‐S batteries in large scale energy storge; 109 refs.